2022
DOI: 10.1002/jclp.23352
|View full text |Cite
|
Sign up to set email alerts
|

Patients' self‐perceived strengths increase during treatment and predict outcome in outpatient cognitive behavioral therapy

Abstract: Objective Modern conceptualizations suggest the independence of positive and negative mental health constructs. Research of positive constructs in psychotherapy is scarce. This study analyzed the development of patients' strengths during psychotherapy and whether pre‐therapy strengths incrementally predict treatment outcome. Methods Two hundred and two patients (56.44% female, mean age = 42.49) treated by 54 therapists underwent cognitive behavioral therapy. Patients' strengths in different contexts as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…We also found a flourishing subgroup consistently high in gratitude and forgiveness throughout treatment (38.7% of the sample) that reported gains in well-being and low depression throughout treatment. This particular finding converges with research showing (a) that greater initial levels of perceived character strengths stemming from prior difficulties predicted lower symptoms and greater well-being at posttest (Schürmann-Vengels et al, 2022) and (b) evidence that a character strengths-reflection intervention improved well-being, particularly among those who showed higher initial levels of well-being (Dolev-Amit et al, 2021). In addition, we found a moderately healthy subgroup that showed a plateau of no change throughout treatment (50.6%).…”
Section: Discussionsupporting
confidence: 88%
“…We also found a flourishing subgroup consistently high in gratitude and forgiveness throughout treatment (38.7% of the sample) that reported gains in well-being and low depression throughout treatment. This particular finding converges with research showing (a) that greater initial levels of perceived character strengths stemming from prior difficulties predicted lower symptoms and greater well-being at posttest (Schürmann-Vengels et al, 2022) and (b) evidence that a character strengths-reflection intervention improved well-being, particularly among those who showed higher initial levels of well-being (Dolev-Amit et al, 2021). In addition, we found a moderately healthy subgroup that showed a plateau of no change throughout treatment (50.6%).…”
Section: Discussionsupporting
confidence: 88%
“…WIRF-CrisesS may be relevant to research that focuses on the description and etiology of mental health in clinical populations, as it seems to be less entwined with psychopathology and, therefore, may contribute to an increase in information ( Bos et al, 2016 ). Moreover, in the context of psychotherapy research, WIRF-CrisesS was found to be a significant predictor of treatment outcome beyond problem-associated measures ( Schürmann-Vengels et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study we will use a total score of resources in the context of current problems (12 items). Item example: “I am dealing with my current difficulties and problems by – actively tackling tasks.” The scale has displayed good internal consistency (α = .88), evidence for convergent and divergent validity as well as evidence of change sensitivity in the course of psychotherapy ( Schürmann-Vengels et al, 2022 ; Victor et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The scale has displayed good internal consistency (α = .88), evidence for convergent and divergent validity as well as evidence of change sensitivity in the course of psychothera py (Schürmann-Vengels et al, 2022;Victor et al, 2019).…”
Section: Intervention Analysis -Primary Outcomementioning
confidence: 99%